Complexation of Cm(III) with monosilicic acid in chloride media - Özyagan, Sema; Warth, Kim; Sittel, Thomas; Panak, Petra (Applied geochemistry, 2025)
In this work, we present a detailed complexation study of Cm(III) with monosilicic acid in a NaCl medium at low to medium ionic strengths (Im = 0.01-3.00 m). The complexation has been monitored using time-resolved laser fluorescence spectroscopy (TRLFS) in the pHm range of 4-6. The results show that the formation of the monosilicate complex, [Cm(H3SiO4)]2+, is decreased with increasing ionic strength, leading to vast changes in the complex stability constant. Using the Specific Ion Interaction Theory (SIT), we were able to determine the complex stability constant at ionic strength Im = 0 with logKm0 = 8.1 ± 0.8 and the binary ion-ion interaction coefficient ε ([Cm(H3SiO4)]2+,Cl−) = 0.40 ± 0.04. Additionally, we studied the complexation at elevated temperatures at low to medium ionic strength. Using the van't Hoff equation, ΔrHm0 = 16.4 ± 0.5 kJ mol−1, ΔrSm0 = 210 ± 21 J K−1 mol−1 and the free Gibbs Energy ΔrGm0 = − 46.2 ± 5 kJ mol−1 have been determined. These results show that the complexation reaction is endothermic and driven by an increase of entropy. These novel results obtained in a wide range of various ionic strengths are very important for the modeling of actinide behavior under near-field conditions of a nuclear waste repository in clay formations containing pore and formation waters with increased ionic strength.
Online verfügbar: 4. Juni 2025, Artikelversion: 9. Juni 2025
Gesehen am 17.10.2025